How does attribute ambiguity improve memory? - Brainerd, C. J.; Chang, M.; Bialer, D. M.; Liu, X. (Memory & cognition, 2023)
The memory effects of semantic attributes (e.g., concreteness, familiarity, valence) have long been studied by manipulating their average perceived intensities, as quantified in word rating norms. The semantic ambiguity hypothesis specifies that the uncertainty as well as the intensity of semantic attributes is processed when words are encoded. Testing that hypothesis requires a normed measure of ambiguity, so that ambiguity and intensity can be manipulated independently. The standard deviation ( SD ) of intensity ratings has been used for that purpose, which has produced three characteristic ambiguity effects. Owing to the recency of such research, fundamental questions remain about the validity of this method of measuring ambiguity and about its process-level effects on memory. In a validity experiment, we found that the rating SD s of six semantic attributes (arousal, concreteness, familiarity, meaningfulness, negative valence, positive valence) passed tests of concurrent and predictive validity. In three memory experiments, we found that manipulating rating SD s had a specific effect on retrieval: It influenced subjects’ ability to use reconstructive retrieval to recall words. That pattern was predicted by the current theoretical explanation of how ambiguity benefits memory.